Mediasi Dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Pasca Berlakunya Peraturan Mahkamah Agung Nomor 1 Tahun 2016: Mediation in Settlement of Divorce Cases in the Religious Courts After the Enactment of Supreme Court Regulation Number 1 of 2016 - Aditama, Maulana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study discusses mediation in the settlement of divorce cases at the Yogyakarta Religious Court after the enactment of the Supreme Court Regulation (PERMA) Number 1 of 2016 concerning Mediation Procedures in Courts. This research is a normative legal research with data obtained through a review of legal literature related to mediation of divorce cases. The nature of this research is descriptive-analytic, using a juridical approach and analyzed using qualitative methods. The results of this study are Perma No. 1 of 2016, which states that Perma No. 1 of 2008 concerning Mediation Procedures in Courts has not been optimal in meeting the needs of carrying out mediation, so it is necessary to make improvements to the Supreme Court regulations regarding mediation procedures in court. The urgency of mediation in this Perma is emphasized in the form of an obligation for the examining judge to order the parties to mediate